2022
DOI: 10.1182/blood.2021013983
|View full text |Cite
|
Sign up to set email alerts
|

TP53 copy number and protein expression inform mutation status across risk categories in acute myeloid leukemia

Abstract: Mutant TP53 is an adverse risk factor in acute myeloid leukemia (AML), but large-scale integrated genomic-proteomic analyses of p53 alterations in AML patients remain limited. We analyzed TP53 mutational status, copy number (CN), and protein expression data in AML (N=528) and provide a compilation of mutation sites and types across disease subgroups among treated and untreated patients. Our analysis shows differential hotspots in subsets of AML and uncovered novel pathogenic variants involving TP53 splice site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
69
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 37 publications
11
69
3
Order By: Relevance
“…Therefore, we considered a higher threshold of ≥7% staining as optimal despite lower sensitivity. In agreement with our findings, a recent study also identified a threshold of ~7% strong p53 staining to predict AML TP53‐ mutational status 12 . This study and ours demonstrate that a higher threshold of p53 staining appears to be necessary to accurately predict mutational status in AML compared to studies predominately evaluating MDS, where a threshold of ~1% strong staining correlates with the presence of a TP53 mutation 5,11 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, we considered a higher threshold of ≥7% staining as optimal despite lower sensitivity. In agreement with our findings, a recent study also identified a threshold of ~7% strong p53 staining to predict AML TP53‐ mutational status 12 . This study and ours demonstrate that a higher threshold of p53 staining appears to be necessary to accurately predict mutational status in AML compared to studies predominately evaluating MDS, where a threshold of ~1% strong staining correlates with the presence of a TP53 mutation 5,11 .…”
Section: Discussionsupporting
confidence: 91%
“…In theory, high VAF should also correlate with both accumulated mutated p53 protein as well as copy number status, and others have found that a VAF >40% is associated with adverse prognosis in AML and could be indicative of copy number loss. 11,12 However, we found no association between VAF and OS and no association between VAF and percent p53 positive cells. Although mutated TP53 results in protein accumulation, different mutations may result in different levels of stability and may not impact accumulation equally.…”
Section: Discussioncontrasting
confidence: 71%
“…This "multi-hit" mutational status results in a neoplastic clone that lacks any residual wild-type p53 protein. Clinical detection of biallelic TP53 alterations is based on sequencing analysis (covering at least exons 4 to 11) [29,32], often coupled with a technique to detect copy number status, usually fluorescence in situ hybridization with a probe set specific for the TP53 locus on 17p13.1 and/or array techniques (e.g., comparative genomic hybridization or single nucleotide polymorphism arrays) [33]. Loss of genetic material at the TP53 locus may also be inferred by next-generation sequencing [29].…”
Section: Mds With Defining Genetic Abnormalitiesmentioning
confidence: 99%
“…32 Pediatric Hematology and Oncology, Hannover Medical School, Hannover, Germany. 33 Departments of Pathology and Oncology, Fudan University, Shanghai, China. 34 Department of Pathology and Laboratory Medicine, University of Pennsylvania, Philadelphia, PA, USA.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Mutations frequently seen in other myeloid neoplasms are less common in PEL, indicating that biallelic loss of TP53 function is a feature of PEL and may play a critical role in the development of PEL. Of note, biallelic TP53 alteration is not specific to PEL and can be seen in other myeloid neoplasms, such as AML 8 and therapy-related MDS. 9 Thus, TP53 mutations alone may not be sufficient to block the differentiation of erythroid lineage and drive pronormoblast proliferation, a pathognomonic feature of PEL.…”
mentioning
confidence: 99%